Increased Innate Lymphoid Cells in Periodontal Tissue of the Murine Model of Periodontitis: The Role of AMP-Activated Protein Kinase and Relevance for the Human Condition - Qin, Xu; Hoda, Md Nasrul; Susin, Cristiano; Wheeler, Julie N.; Marshall, Brendan; Perry, Libby; Saad, Nancy; Yin, Lin; Elsayed, Ranya; Elsalanty, Mohammed; Abdelsayed, Rafik; Yu, Jack C.; et al. (Frontiers in Immunology, 2017)
Innate lymphoid cells (ILCs) are master regulators of immune and inflammatory responses but their own regulatory mechanisms and functional roles of their subtypes (i.e., ILC1s-ILC3s) remain largely unresolved. Interestingly, AMP-Activated Protein Kinase (AMPK), influences inflammatory responses but its role in modulation of ILCs is not known. Periodontitis is a prevalent disorder with impairment of immune and inflammatory responses contributing importantly to its pathogenesis; however, neither the role of ILCs nor AMPK has been explored in this condition. We tested the hypotheses that a) periodontitis increases ILCs and expression of relevant cytokines thereby contributing to inflammation and b) knockdown of AMPK worsens indices of periodontitis in association with further increases in subtypes of ILCs and cytokine expression. The studies utilized wild type and AMPK knockout (KO) mice, subjected to ligature-induced periodontitis or sham operation, in association with the use of micro-CT for assessment of bone loss, immunogold electron microscopy to show presence of ILCs in periodontal tissues, flow cytometry for quantitative assessment of subtypes of ILCs and RT-PCR analyses to measure mRNA expression of several relevant cytokines. The results for the first time show a) presence of each subtype of ILCs in periodontal tissues of sham control and periodontitis animals, b) that periodontitis is associated with increased frequencies of ILC1s-ILC3s with the effect more marked for ILC2s and differential phenotypic marker expression for ILC3s, c) that AMPK KO mice display exacerbation of indices of periodontitis in association with further increases in the frequency of subtypes of ILCs with persistence of ILC2s effect and d) that periodontitis increased mRNA for interleukin (IL)-33, but not IL-5 or IL-13, in wild type mice but expression of these cytokines was markedly increased in AMPK KO mice with periodontitis. Subsequently, we showed that human periodontitis is associated with increases in each ILCs subtype with the effect more marked for ILC2s and that mRNA expressions for IL-33 and IL-5 are markedly greater for sites affected by periodontitis than healthy sites. Collectively, these novel observations indicate a pivotal role for ILCs in pathogenesis of periodontitis and that AMPK is a regulator of their phenotype expression in this condition.